Synthetic biological approaches in PET biodegradation and bioplastic conversion: Current advances and future perspectives - Castillo, Pearl P. (Animo Repository, 2023)
The global accumulation of waste polyethylene terephthalate (PET) and its resistance to natural degradation gives rise to environmental and health concerns. Synthetic biology offers the potential to further develop microorganisms to achieve this; thus, biodegradation is seen as an ecologically feasible alternative. Hence, there is a need to examine the current progress of this field and how it relates to PET biodegradation along with trends that future research may lean into. We conducted a systematic literature review via Scopus WebSearch, ResearchGate, and Google Scholar, indicating that research on synthetic biology relating to PET biodegradation took off in 2008. A bibliometric analysis was utilized to supplement the study using the Scopus database with a predetermined criteria and journal articles dated January 2008 to November 2023, yielding 429 journal articles, converted into RIS format then processed in Cortext Manager. We found major interest leaned into four clusters: E. coli, microbial consortia, synthetic biology, and P. putida. Current literature emphasizes the metabolic engineering of hydrolase enzymes, like bis-(2-hydroxyethyl) terephthalate (BHET) mono-(2-hydroxyethyl) terephthalate (MHET), that breakdown PET polymers into ethylene glycol (EG) & terephthalic acid (TPA) monomers, with E. coli and P. putida able to further metabolize these derivatives into polyhydroxyalkanoates (PHAs). The data linkages showed that studies trended towards collecting these microorganisms into artificial microbial consortia to increase degradation output. We realized the potential to upcycle PET waste by utilizing these enzymes and microbial consortia to process PET into PHA, a material utilized in pharmaceutics and the emerging tissue engineering field.